Application of Dayak Onion (Eleutherine bulbosa Urb.) as a Preservative for Animal Protein: Chicken Meat - Riadh, Dellysa Naomi; Paramita, Swandari; Yadi (Future Science / FSH-PH Publications, 2024)
The adoption of chicken meat as the primary protein source remains limited in Indonesia due to restrictions on its shelf life. Marinating chicken meat with Dayak onion, known for its antibacterial and antioxidant characteristics, can prolong the meat's shelf life. This research evaluates the efficacy of Dayak onion as a natural preservative for animal protein, specifically chicken meat. The study used a qualitative experimental design featuring both control and treatment groups. The experiment involved testing the pH value and cooking loss value of chicken meat that has been marinated with Dayak onion powder (treatment) and chicken meat that had not been marinated (control). The process of data analysis commenced with the application of the Saphiro-Wilk Test to ascertain the nature of the distribution. If the distribution is found to be normal, the subsequent step involves conducting the Independent-T test. Conversely, if the distribution is determined to be non-normal, the Mann-Whitney Test is employed instead. The research findings indicated that Dayak onion has a notable effect on maintaining the pH level of chicken flesh after 9 hours, as opposed to untreated chicken meat (p0.05). The overall findings demonstrate the capacity of Dayak onion as an organic preservative for chicken meat.